Intravenous Ibuprofen Reduces Opioid Consumption During the Initial 48 Hours After Injury in Orthopedic Trauma Patients. Issue 7 (July 2020) - Weisz, Russell D.; Fokin, Alexander A.; Lerner, Vivian; Flynt, Amy; Macias-Perez, Ines; Pavliv, Leo; Crawford, Maggie; Puente, Ivan
Abstract : Objectives: To evaluate the efficacy of intravenous (IV) ibuprofen (Caldolor) administration in the management of acute pain in orthopedic trauma patients and to minimize opioid use. Design: Randomized controlled trial, double-blind, parallel, placebo-controlled. Setting: Level 1 Trauma Center. Patients: A total of 99 consecutive orthopedic trauma patients with fractures of the ribs, face, extremities, and/or pelvis were randomized to receive either 800 mg IV ibuprofen (53 patients) or placebo (44 patients) administered every 6 hours for a total of 8 doses within 48 hours of admission and the same PRN medications along with 20-mg IV/PO Pepcid twice a day. To establish pain reduction efficacy, the analysis was consequently performed in the modified intent-to-treat group that included 74 randomized subjects with a baseline pain score greater than 2. The primary outcomes were reduction in opioid consumption and decrease in pain intensity (PI). Intervention: Administration of study medications. Outcome Measurements: PI measured by Numerical Rating Scale, opioid consumption adjusted to morphine equivalent dose, and time to first narcotic administration. Results: The 2 groups had comparable baseline characteristics: age, sex distribution, mechanism of injury, type of injury, injury severity score, and PI. IV ibuprofen statistically significantly reduced opioid consumption compared with placebo during the initial 48-hour period ( P = 0.017). PI calculated as PI differences was statistically different only at 8-hour interval after Caldolor administration. Time to first narcotic medication was significantly longer in the Caldolor group (hazard ratio: 1.640; 95% confidence interval, 1.009–2.665; P = 0.046). Conclusions: IV ibuprofen provided adequate analgesia, prolonged time to first narcotic administration, and was opioid-sparing for the treatment of pain in orthopedic trauma patients, which makes Caldolor a recommended candidate for managing acute pain in the diverse orthopaedic trauma population. Level of Evidence: Therapeutic Level I. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.